Pengaruh Kepemimpinan Transformasional Terhadap Komitmen Organisasional Pada Pimpinan Wilayah Muhammadiyah (PWM) Riau - Muhammad Fikry Hadi; Risnal Diansyah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
The role of human resource management in an organization or union is a guarantee for the union in achieving its objectives. In a study to measure organizational commitment consists of three things, namely: affective commitment associated with the level of an employee emotionally bound, involved and familiar with the organization; Continuous commitment is an assessment of the costs associated with leaving the organization. Based on the research, it can be concluded that transformational leadership in the form of charisma has no influence on organizational commitment in Muhammadiyah Regional Leadership Riau Province, as well as inspirational motivation, does not give influence to organizational commitment of Muhammadiyah Regional Leadership. while intellectual stimulation, and individualized consideration has a positive influence on organizational commitment to the Regional Leadership of Muhammadiyah Riau Province. Thus, Members of the Muhammadiyah organization are committed because of their Muhammadiyah Organization, not the views of their individual leaders, especially charism and intellectual stimulation.